(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2022)
Medication discrepancies are of great concern in hospitals because they pose risks to patients and increase health care costs. The aim of this study was to estimate the prevalence of inconsistent medication prescriptions to adult patients admitted to a hospital in southern Santa Catarina, Brazil. This was a patient safety study on patients recruited between November 2015 and June 2016. The participants were interviewed and had their medical records reviewed. Discrepant medications were considered those that did not match between the list of medicines taken at home and the prescribed drugs for treatment in a hospital setting. Of the 394 patients included, 98.5% took continuous-use medications at home, with an average of 5.5 medications per patient. Discrepancies totaled 80.2%, The independent variables associated with the discrepancies were systemic arterial hypertension, hypercholesterolemia, vascular disease, number of medications taken at home, and poor documentation of the medications in the medical record. Findings from this study allowed us to conclude there was a high rate of prescription medication misuse. Medication reconciliation is crucial in reducing these errors. Pharmacists can help reduce these medication-related errors and the associated risks and complications.